Design and synthesis of dephosphono dna analogues containing 1,2,3-triazole linker and their UV-melting studies with DNA/RNA - Madhuri, Vangala; Kumar, Vaijayanti A. (Nucleosides Nucleotides & Nucleic Acids, 2012)
This article describes the synthesis of 3'/5' linked 1,2,3-triazolyl dithymidine derivatives, their incorporation into oligonucleotides, and evaluation of their thermal stabilities toward complementary DNA/RNA.
Keywords: isostere; Oligonucleotide analogues; Triazole; UV melting